LU-177-PSMA TREATMENT FOR METASTATIC PROSTATE CANCER – CASE EXAMPLES OF MIRACLE RESPONSES - K. Kairemo; T. Joensuu (Вестник урологии, 2018)
Prostate specific membrane antigen (PSMA) is expressed in unfavorable prostate cancer. PSMA is basis for new diagnostics and theranostics. 177Lu-PSMA radioligand therapy is mainly used for patients with endstage prostate cancer. This report describes two patients: one patient with a multiple recurrences and one with extensive metastastic disease during the first visit. Both these patients were treated with 177Lu-PSMA radioligand therapy with major response, i.e. complete response by imaging and substantial reduction of PSA. 177Lu-PSMA radioligand therapy gave only mild adverse effects. In conclusion, patients with metastatic prostate cancer, 177Lu-PSMA-617 radioligand therapy had an attractive therapeutic profile which had to be adjusted according to the patient´s need.